The Mysteries of Our Existence: Estrangement and Theatricality - Carnes, Natalie (Modern theology, 2012)
"Theater" has become a fashionable metaphor that theologians and ethicists deploy to correct what they see as a Gnostic or antinomian impulse to prioritize "inner state" over "outer action." But their turn to theater as an easy way to valorize "outer action" conflates person and role, generating a confused anthropology that 1) obscures what theater could make obvious about occupational roles; 2) misses the distinctively non-theatrical character of performing Christ and church; and 3) renders actions more easily legible than they in fact are. These losses are traced in the work of several theater theologians, and their resultant distortions in self, power, and freedom are elaborated with the help of Stephen Mulhall's critique of Alasdair MacIntyre and Charles Taylor. Gregory of Nyssa's use of theater, by contrast, avoids such distortions by invoking theater together with the "mysteries of our existence"—death and creatio ex nihilo. Theater, for Gregory, becomes a way to describe the estrangement Christians must live into in a world beholden to wealth and power. The anthropology embedded in his metaphor of theater elaborates how Christians might approach their occupational roles, the world, and skepticism.